(untitled) (Progressive Agriculture, 2014)
Dhaka Zoo with 2000 animal heads of 184 species from significant genetic diversity and five million visitors influx round the year is placing it a public health important spot. This study was conducted to investigate cryptococcosis in animals at Dhaka Zoo to ascertain animal health, welfare and public health safety standard. One hundred and two opportunistic tissue samples were collected and preserved in 10% neutral buffered formalin at necropsy for 36 animals of 25 different species from Dhaka Zoo during the study period. Twenty five among the study animals were found suffering from granulomatous diseases, of them nine cases were identified cryptococcosis first ever in Bangladesh. Clinical history, nodular lesions on necropsy findings, granulomatous reactions with fungal spores & both Langhangs & foreign body giant cells on histopathology and characteristic spores with wide gelatinous band around endospores on special staining revealed cryptococcosis in eight rhesus macaques (Macaca mulatta) and one greater kudu (Tragelaphus strepsiceros). Present study provides evidence of existing cryptococcosis and similar long standing zoonotic diseases in majority of rest of the animals with health risk that shades health safety standard at Dhaka zoo. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19114 Progress. Agric. 24(1&2): 123 - 129, 2013